2016
DOI: 10.3727/096368916x690458
|View full text |Cite
|
Sign up to set email alerts
|

The Cytoprotective Effects of Human Endothelial Progenitor Cell-Conditioned Medium against an Ischemic Insult Are Not Dependent on VEGF and IL-8

Abstract: Endothelial progenitor cells (EPCs) promote revascularization and tissue repair mainly by paracrine actions. In the present study, we investigated whether EPC-secreted factors in the form of conditioned medium (EPC-CM) can protect cultured brain microvascular endothelial cells against an ischemic insult. Furthermore, we addressed the type of factors that are involved in the EPC-CM-mediated functions. For that purpose, rat brain-derived endothelial cells (rBCEC4 cell line) were exposed to EPC-CM pretreated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…To eliminate the proteinaceous content in the CM, the CM was treated with proteinase K as described earlier 5,12 . In brief, aliquots of EBM-2 or CM medium were incubated with agarose beads-proteinase K (Sigma, Buchs, Switzerland; 5 U) in 15 ml polypropylene test tubes (BD Falcon, Allschwil, Switzerland) for 4 h at 37°C in a rotating roller drum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To eliminate the proteinaceous content in the CM, the CM was treated with proteinase K as described earlier 5,12 . In brief, aliquots of EBM-2 or CM medium were incubated with agarose beads-proteinase K (Sigma, Buchs, Switzerland; 5 U) in 15 ml polypropylene test tubes (BD Falcon, Allschwil, Switzerland) for 4 h at 37°C in a rotating roller drum.…”
Section: Methodsmentioning
confidence: 99%
“…Thereafter, the tubes were centrifuged 5 min at 2000 rpm to pellet the agarose beads-proteinase K, and the proteinase K-free supernatant was carefully collected and used for subsequent experiments. The treatment resulted in degradation of proteins as assessed in Coomassie Blue (Sigma, Buchs, Switzerland)-stained gels 5,12 (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…*p < .05, **p < .01, ***p < .001 [Colour figure can be viewed at wileyonlinelibrary.com] function. Various studies have shown that the cytoprotective and angiogenic properties of EPCs substantially rely on paracrine mechanisms (Di Santo, Fuchs, Periasamy, Seiler, & Widmer, 2016;Odent Grigorescu et al, 2017;Rosell et al, 2013;Yang et al, 2010;Zhang et al, 2014). Burchfield and Dimmeler showed that the beneficial effect of EPC transplantation on diabetic wounds was mainly achieved by their paracrine action on keratinocytes, fibroblasts, and endothelial cells (Burchfield & Dimmeler, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, our earlier study identified lipidic factors as important mediators of the actions of EPC-CM 7 . Moreover, we have previously shown that EPC-CM contains a number of neurotrophic factors including brain-derived neurotrophic factor glial cell line-derived neurotrophic factor, neuritin, and vascular endothelial growth factor, which are critical for the developing cerebral cortex 8 , 30 . In addition, it has been reported that EPC secretome has the capacity to promote oligodendrocyte expansion and maturation in mice in a model of cerebral hypoperfusion 6 .…”
Section: Discussionmentioning
confidence: 99%